Grafites feministas: espaço de luta e resistência na arte urbana (2000-2018) - Freitas, Nathália de (2019)
Since the 1960’s the contemporary urban art has been an instrument of protest. Movements of workers, students, artists and black people of both genders used and keep using the streets to question the established order, politics and the society in general. “Feminist graphites: space of struggle and resistance in urban art (2000-2018)” aproaches the urban art scenario as a women protest space, especially in Brazil, and do it by analyzing the works made by women and men who raise topics and problems taken as relevant for women’s issues. Among those topics there are violence against women, maternity, blackness, empowerment, sorority, feminine power, racism etc. The analyzed graphites also approach legislative landmarks which contemplate women’s cause such as the laws 11.340/2006 and 13.104/2015 known as Law Maria da Penha and Law of Feminicide, respectively. The study also includes graphites which commemorate characters who made history and became references to women’s struggle such as Simone de Beauvoir, Nina Simone, Malala Yousafzai, Marielle Franco, Maria Bonita, Anne Frank and Frida Kahlo as well as super heroines from fiction such as Bat Girl and Wonder Woman. The artists’ performance is important for reflections which allow new visibilities about gender issues and contribute significantly to the formation of a women’s narrative, in other words, the graphites give voice to the feminist movement and to the women’s history itself which is often forgotten by the dominant and sexist historiography. The feminist graphite is a work of protagonism, struggle and women’s resistance in History and also a legitimate way of giving visibility to the plurality of the movement.